Sistema de controle para termociclador - Corte, Angélico (Universidade do Vale do Rio dos Sinos, 2016)
The thermocycler is an equipment used to perform a molecular biology technique called PCR (Polymerase Chain Reaction), which aims at amplifying target DNA fragments. It is widely used in biology, health and agriculture sciences, animal, plant and human diagnostics, as well as in forensics. The equipment completes variable temperature cycles, and the success of the technique relies on three factors: (1) increasing and decreasing ramp rates; (2) temperature accuracy and stability of the temperatures set in the program; (3) a reduced overshoot at the end of each temperature ramp. This research was developed as the first phase of a Technology Nationalization Project. The aim was to identify the best controller to regulate temperature in thermal cycles and assemble a prototype of such equipment. The controllers tested were PID(Generic, ISA, Parallel and Dahlin Synthesis) andGMV. These controllers were simulated using Matlab and then, implemented in a hardware system. The following improvements were implemented in the Dahlin PID Controller during this work: addition of two gain variables in the proportional component, an extra proportional component, one saturator and a filter to accelerate the decreasing ramp. Such improvements allowed us to solve the problems of the controllers, as none of them presented acceptable results in its original form. The prototype was assembled and tested in the Molecular Biology Laboratory of Unisinos. The PCR results obtained with the prototype were equivalent as those obtained from the imported equipment used regularly in the laboratory.
Keywords: Termociclador; Controlador GMV; Biologia molecular; PCR; Controlador PID; PID de Dahlin; Thermocycler; PID controller; Dahlin PID; GMV Controller; Molecular biology; ACCNPQ::Engenharias::Engenharia Elétrica